SEARCH OF WAYS TO SOLVE THE PROBLEM OF TRANSFORMATION OF NATIONAL STATEMENTS IN ACCORDANCE WITH INTERNATIONAL REQUIREMENTS - E. V. Shemeleva; V. P. Kuznecov; N. E. Grechkina (Вестник Мининского университета, 2017)
Implementation of innovative projects require additional investments, which confirmed the feasibility of objective, accurate and comprehensible to the investor's financial reporting. The article substantiates necessity of transformation of financial statements in accordance with International Financial Reporting Standards (IFRS) in order to increase the investment attractiveness of domestic companies to foreign investors. An algorithm for the transformation, the essence of which is to consistently identify differences in the accounting of national and international standards, and making the appropriate adjustments to the national reporting to conform with IFRS. The transformation of a complex, multi-faceted and creative process that requires in-depth knowledge and the availability of professional competence in those responsible for his conduct of employees. But it allows you to get financial statements that comply with international standards, without the organization of a parallel accounting system, which significantly reduces the cost to develop and increase the investment attractiveness and competitiveness of domestic enterprises.